The effect of ENSO / Anti ENSO on northeast monsoon rainfall - DE , U. S.; MUKHOPADHYAY, R. K. (MAUSAM, 1999)
Northeast monsoon precipitation data of 5 meteorological sub-divisions in India, spanning the period 1901-97, were analysed to identify the effect of ENSO/Anti ENSO events on the rainfall over southern peninsular India. ENSO/Anti ENSO years were selected on the basis of seasonal Southern Oscillation Index (SOI). The analysis revealed that ENSO years were generally associated with enhanced northeast monsoon precipitation while there was reduced precipitation during Anti ENSO years, the reduction in Anti ENSO years being significant for Tamil Nadu (at 0.1% level), for Kerala (at 1% level) and for South Peninsular India (at 1% level). Of 22 ENSO years, 18 years were found to be either flood or wet years, while 11 years out of 15 Anti ENSO years were found to be either drought or dry years. During ENSO years, the Sea Surface Temperature (SST) anomalies both over the Arabian Sea and the Bay of Bengal were positive during the months October to December, while the reverse was the case during Anti ENSO years. A concurrent significant positive correlation was noted between SST over east central Arabian Sea and the north central Bay regions and northeast monsoon rainfall. The cyclonic systems were observed to form relatively at lower latitudes during ENSO years as compared to those during Anti ENSO years. These systems were also found to move in a more westerly direction, hit Tamil Nadu and south Andhra coast, thus giving more rain over peninsula during ENSO years. The ridge line at 200 hPa level during ENSO years was located 3° south as compared to its location during Anti ENSO years.